Women and Household Welfare in Kasese Municipality: A Case Study of Central Division Kasese Municipality. - Bukenya, Gilbert (Kabale University, 2025)
The purpose of the study was to establish the women and household welfare in Kasese Municipality with a specific focus on the central division in Kasese Municipality. The study was guided by specific objectives: to find out the nature of problems faced by female-headed households inthe central division, Kasese Municipality, to examine the factors leading to women household heads in the central division, Kasese Municipality, and to find out the challenges faced by female-headed household in central division Kasese Municipality.